1976
DOI: 10.1021/ja00436a047
|View full text |Cite
|
Sign up to set email alerts
|

Proton magnetic resonance studies of sym-oxepin oxide

Abstract: syw-oxepin oxide (1) in aprotic solvents (CDCI3, CH2CI2, CD2CI2, THF, or CH3CN) with catalytic amounts of MeSOsH led within seconds to the generation of 13. In CDCI3 the addition of MeSC^H (0.1 mol %) catalyzes the quantitative ( NMR) rearrangement of 1 to 13: ir (CDC13) 1725, 1680, 1620, 1260 cm-'; NMR (CDC13, 100 MHz) 9.51 (1 H, d), 6.50 (2 H, m), 4.90 (2 H, m), 3.64 (1 H, m); uv (CH3CN) Xmax 246 (e 590), 310 (110); mass spectrum (70 eV) m/e parent 110, base 81. Exact mass of p-nitrophenylhydrazone: cale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1979
1979
1997
1997

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 9 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Thus, demetalation of the copper(I) complex 4 was performed with 20% aqueous ammonia in the temperature range −20 to −30 °C, to liberate the azo diepoxide 5 . This underwent decomposition in CDCl 3 at room temperature, with extrusion of nitrogen, to give sym -oxepin oxide 3b (see Scheme ): 1 H NMR (200 MHz, CDCl 3 ) δ 6.34 (2H, d), 5.14 (2H, ddd), 3.33 (2H, dd) (see ref for analysis of this spin system). The solvent was removed (−42 °C at 0.02 mmHg) and the residual sym -oxepin oxide ( 3b ) was taken up in deuterated acetone: 1 H NMR (200 MHz, acetone- d 6 ) δ 6.54 (2H, d, J = 7.5 Hz, 2-H, 7-H), 5.33 (2H, ddd, J = 2.1, 3.5, 7.5 Hz, 3-H, 6-H), 3.43 (2H, dd, J = 2.1, 3.5 Hz, 4-H, 5-H).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, demetalation of the copper(I) complex 4 was performed with 20% aqueous ammonia in the temperature range −20 to −30 °C, to liberate the azo diepoxide 5 . This underwent decomposition in CDCl 3 at room temperature, with extrusion of nitrogen, to give sym -oxepin oxide 3b (see Scheme ): 1 H NMR (200 MHz, CDCl 3 ) δ 6.34 (2H, d), 5.14 (2H, ddd), 3.33 (2H, dd) (see ref for analysis of this spin system). The solvent was removed (−42 °C at 0.02 mmHg) and the residual sym -oxepin oxide ( 3b ) was taken up in deuterated acetone: 1 H NMR (200 MHz, acetone- d 6 ) δ 6.54 (2H, d, J = 7.5 Hz, 2-H, 7-H), 5.33 (2H, ddd, J = 2.1, 3.5, 7.5 Hz, 3-H, 6-H), 3.43 (2H, dd, J = 2.1, 3.5 Hz, 4-H, 5-H).…”
Section: Methodsmentioning
confidence: 99%
“…H NMR). Data for 15c: NMR (py-ds) (Me4Si) 1.68 (m, 10 H), 4.91 (d, J = 7 Hz, 2 H), 6.28 (d, J = 7 Hz, 2 H): IR (py-t/5) 1675, 1656 cm-1…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, we detailed3 our conversion of benzene oxide oxepin to sym-oxepin oxide (3, R = H, Scheme II), and studied the conformation and Cope rearrangement of 3 (R = H) by NMR spectroscopy. 4 Other studies revealed the Cope rearrangement of a methylated derivative5 and helped define the scope6 of our synthetic approach to oxepin oxides. Further, we reported the synthesis of the bridgehead diene 10a7 (Scheme IV) and characterized a derivative of 10a by X-ray crystal analysis.8…”
mentioning
confidence: 96%
See 1 more Smart Citation